Agustín Viesca governador constitucional del Estado Libre de Coahuila y Texas : por el Ministerio de Relaciones, se me há comunicado la resolución que sigue. Primera Secretaría de Estado, Departamento del Exterior . ([publisher not identified], 1835)
Notification from the Minister of Foreign Affairs that a recently passed state law is in conflict with a federal law. Whereupon, Governor Viesca issued this broadside to notify the public of the conflict.